The Effectiveness of Self-talk in Increasing Client's Self-Efficacy at the Baddoka Makassar BNN Rehabilitation Center - Citra, Yulia; Daud, Muhammad; Indahari, Nur Afni (Jurnal Psikologi Karakter, 2022)
Low self-efficacy is a problem that hinders the success of addicts to leave drugs. Self-talk is one form of intervention that can affect the increase in self-efficacy in drug addicts. This study aims to determine the effectiveness of self-talk in increasing the self-efficacy of clients undergoing rehabilitation programs at BNN Baddoka Makassar. This research is a quasi-experimental one-group pretest-posttest design. This study used 5 subjects who were drug addicts with very low minimum self-efficacy. The measuring instrument used in this study is a self-efficacy scale adapted from Supriyanto and Hendiani, showing a reliability value of 0.905. This study uses nonparametric statistical analysis Wilcoxon test. The results of the study indicate that self-talk is effective in increasing the client's self-efficacy at the BNN Baddoka Makassar rehabilitation center, the results can be seen from the significant difference between the self-efficacy scores of the pretest and posttest (W= 0.00, p=0.015). Subjects in this study experienced an increase in self-efficacy scores. Thus, self-talk can be used to increase the self-efficacy of drug addicts.